Increased crop productivity, regional trade & income for smallholder farmers in Tanzania (SSUCORETA) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
In Tanzania, the SSUCORETA Project has enhanced the capabilities of local business partners and small-scale cassava and sunflower farmers. This was achieved by providing innovative technology, training, and establishing partnerships with organizations from the Global South. These efforts aim to boost productivity and facilitate access to regional trade for the farmers.